2009
DOI: 10.14710/jitaa.34.3.196-204
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary Feeding on the Nutrient Balance of Lactating Dairy Cow at Contrasting Temperature Regimes: Assessment Using Cornell Net Carbohydrate and Protein System (Cncps) Model

Abstract: Dairy cows often do not receive adequate nutrient supply during their lactation period. This condition can even be worse if the environmental temperature is not in comfortable range which may occur especially in tropical regions. The present research was aimed to simulate the effect of supplementary feeding on nutrient balance of lactating dairy cow at contrasting temperature regimes using Cornell Net Carbohydrate and Protein System (CNCPS) model. Treatments consisted of feeds (R1: Pennisetum purpureum, R2: P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Supplementation to forage based diet is necessary to provide adequate nutrient supply, especially for high producing ruminants (Jayanegara and Sofyan, 2009). So far concentrate is the commonest supplement used (Bargo et al, 2002;Steinshamn et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementation to forage based diet is necessary to provide adequate nutrient supply, especially for high producing ruminants (Jayanegara and Sofyan, 2009). So far concentrate is the commonest supplement used (Bargo et al, 2002;Steinshamn et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, high cost of concentrate may limit its use as a supplement particularly for small-holder farmers and, therefore, alternative supplement needs to be introduced. Although it has been shown that some alternative supplements from Leucaena leucocephala and Gliricidia sepium leaves were inferior as compared to conventional concentrate (Jayanegara and Sofyan, 2009), screening of such alternative supplements from plant leaves is important to be further extended.…”
Section: Introductionmentioning
confidence: 99%